Recycling in the Haua Fteah sequence of North Africa. (10th March 2015) - Hiscock, Peter
Abstract: A study of lithic artefacts at Haua Fteah, North Africa, documents the recycling of scrapers and burins during the period 70–15, 000 BP. Rates of recycling are high during the Middle and Upper Palaeolithic but far lower during the post-LGM Epi-palaeolithic industry. These data indicate that factors other than cognitive capacity and 'modern behaviour' can be responsible for creating industries structured around reworking/recycling or around formalised and distinctive implement forms. In the case of Haua Fteah the proposed explanation is a shift to lithic production focussed on craft specialists in the Epi-palaeolithic, with an accompanying shift to strong normative views about socially acceptable tool forms, and probably increased functional specificity in tool use.